Early antibiotics and risk for necrotizing enterocolitis in premature infants: A narrative review - Cuna, Alain; Morowitz, Michael J.; Sampath, Venkatesh (Frontiers in Pediatrics, 2023)
While prompt initiation of antibiotics at birth is important for preventing early onset sepsis, it often leads to many preterm infants being exposed to treatment despite negative blood cultures. Such exposure to early antibiotics can impact the developing gut microbiome putting infants at increased risk of several diseases. Necrotizing enterocolitis (NEC), a devastating inflammatory bowel disease that affects preterm infants, is among the most widely studied neonatal disease that has been linked to early antibiotics. While some studies have demonstrated an increased risk of NEC, other studies have demonstrated seemingly contrary findings of decreased NEC with early antibiotics. Studies using animal models have also yielded differing findings of benefit versus harm of early antibiotic exposure on subsequent NEC susceptibility. We thus sought to conduct this narrative review to help clarify the relationship between early antibiotics exposure and future risk of NEC in preterm infants. Our objectives are to: (1) summarize findings from human and animal studies that investigated the relationship between early antibiotics and NEC, (2) highlight important limitations of these studies, (3) explore potential mechanisms that can explain why early antibiotics may increase or decrease NEC risk, and (4) identify future directions for research.